Biochemical markers and assessment of cardiotoxicity during preparative regimen and hematopoietic cell transplantation in acute leukemia - Horacek, J M; Pudil, R; Tichy, M; Jebavy, L; Zak, P; Slovacek, L; Maly, J (Experimental oncology, 2007)
INTRODUCTION: Cardiotoxicity is a relatively frequent and potentially serious complication of antitumor treatment. Anthracyclines and other high-dose chemotherapy represent the greatest risk. The aim of the study was to assess cardiotoxicity during preparative regimen (PR) and hematopoietic cell transplantation (HCT) in acute leukemia (AL) with biochemical markers - "N-terminal pro brain natriuretic peptide" (NT-proBNP), cardiac troponin T (cTnT) and creatine kinase MB (CK-MB mass). METHODS: Nineteen adult AL patients previously treated with anthracyclines--idarubicine, daunorubicine, mitoxantrone with standard doses for a cycle as 3 x 12 mg/m(2), 3 x 50 mg/m(2), 3 x 10 mg/m(2) accordingly were studied. PR consisted of high-dose cyclophosphamide (HD-C) in combination with busulphan or total body irradiation (TBI). Plasma NT-proBNP, cTnT and CK-MB mass concentrations were measured the day before PR, the day after PR, the day after HCT and 14 days after HCT. RESULTS: Before PR, mean plasma NT-proBNP value was 106.3+/-55.7 ng/l. After PR, it increased to 426.1+/-391.5 ng/l. After HCT, a further increase to 847.6+/-780.6 ng/l was observed. Fourteen days after HCT, the mean NT-proBNP was 330.8+/-236.8 ng/l. The differences were statistically significant in comparison with the baseline values (p<0.01). The NT-proBNP elevations were more pronounced in patients with cumulative doses (CD) of anthracyclines above 450 mg/m(2) (p<0.05), in patients with PR containing HD-C and TBI (p<0.05). In all patients, plasma cTnT and CK-MB mass concentrations remained unchangable during PR and HCT. CONCLUSION: Our results suggest that administration of PR and HCT is in most AL patients associated with acute neurohumoral activation (significant rise in NT-proBNP). Persistent NT-proBNP elevations, in our study in 12 (63.2%) patients, indicate subclinical cardiotoxicity (risk for development of heart failure) and require further follow-up. More pronounced NT-proBNP elevations in patients with higher CD of anthracyclines and in patients with PR containing combination of HD-C and TBI confirm that these therapeutic procedures seem to be more cardiotoxic and not very appropriate for patients with cumulation of risk factors for cardiotoxicity. Negative plasma cTnT and CK-MB mass concentrations show no detectable damage of cardiomyocyte structure during PR and HCT.
Keywords: Echocardiography; kreatinkinasa, forma MB; mužské pohlaví; Male; Hematopoietic Stem Cell Transplantation; Anthracyclines; Troponin T; Leukemia; Female; Humans; natriuretický peptid typu B; lidé; echokardiografie; peptidové fragmenty; ženské pohlaví; Myeloablative Agonists; Acute Disease; akutní nemoc; troponin T; transplantace hematopoetických kmenových buněk; Biomarkers; biologické markery; antracykliny; Heart Diseases; Peptide Fragments; myeloablativní agonisté; dospělí; nemoci srdce; Adult; leukemie; Creatine Kinase, MB Form; Natriuretic Peptide, Brain